Penegakan Hukum terhadap Prostitusi Anak Melalui Media dalam Jaringan Online : Studi Kasus di Kepolisian Resor Kota Besar Surabaya - Nurhijah Nurhijah (Pusat Riset dan Inovasi Nasional, 2022)
The factors that cause a person to commit a crime of prostitution, mostly lies in economic factors and social factors, economic factors are influenced by one's income or needs, while social factors are influenced by environmental conditions, the environment and one's education. Law enforcement on child prostitution cases through online media networks that occurred recently in the Kepolisisan jurisdiction of the Surabaya Big City Resort only uses Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, Article 15, Article 59 paragraphs (1) (2), article 76F, and article 83 to ensnare child prostitutes through the media in online networks. This type of research is empirical research that discusses the problem of interview results based on the current legal regulations and then relates to the facts available for further discussion regarding law enforcement against child prostitution through online media using Law Enforcement Theory in terms of legal substance. Legal structure and legal culture, also uses criminal policy theory.